2021
DOI: 10.3390/coatings11111426
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Acid-Etching on Grit-Blasted Dental Implants to Improve Osseointegration: Histomorphometric Analysis of the Bone-Implant Contact in the Rabbit Tibia Model

Abstract: Previous studies have shown that the most reliable way to evaluate the success of an implant is by bone-to-implant contact (BIC). Recent techniques allow modifications to the implant surface that improve mechanical and biological characteristics, and also upgrade osseointegration. Objective: The aim was to evaluate the osseointegration in rabbit tibia of two different titanium dental implant surfaces: shot-blasted with Al2O3 (SB) and the same treatment with an acid-etching by immersion for 15 s in HCl/H2SO4 (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
2
1
0
Order By: Relevance
“…Although the measurement of implant stability through micro-CT or ISQ is non-invasive, it has the disadvantage that osseointegration cannot be confirmed as directly as histological investigation. Histological BIC ratio in the present study was similar to that of other studies (35.16% by Kfouri et al [ 29 ], 45.2% by Yeo et al [ 32 ] and 59.9% by Rios-Carrosco et al [ 33 ]), and histological observations confirmed that proper osseointegration was gained, directly. However, compared to micro-CT or ISQ measurement, histological observation has a limitation that the result value may be different depending on which part is used as a sample, so the results should be interpreted with caution.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although the measurement of implant stability through micro-CT or ISQ is non-invasive, it has the disadvantage that osseointegration cannot be confirmed as directly as histological investigation. Histological BIC ratio in the present study was similar to that of other studies (35.16% by Kfouri et al [ 29 ], 45.2% by Yeo et al [ 32 ] and 59.9% by Rios-Carrosco et al [ 33 ]), and histological observations confirmed that proper osseointegration was gained, directly. However, compared to micro-CT or ISQ measurement, histological observation has a limitation that the result value may be different depending on which part is used as a sample, so the results should be interpreted with caution.…”
Section: Discussionsupporting
confidence: 92%
“…Both groups showed significant intragroup differences in the ISQ values measured immediately after implant placement, and at one month after implant placement, indicating that osseointegration progressed adequately at one month after implant placement in both groups. The ISQ values measured after 6 weeks were similar to those of other studies (68~70 by Yeo et al [ 32 ] and 73~78 by Rios-Carasco et al [ 33 ]), and through this, proper implant stability to withstand loading was achieved. Immediately after surgery, a higher ISQ value was noted in the experimental group than in the control group; however, at one month after surgery, both groups showed similar ISQ values.…”
Section: Discussionsupporting
confidence: 88%
“…This surface generally presents important residual stress values due to the impact of the abrasive particles that have caused plastic deformation on the surface. The stresses suffered in these areas due to friction between the cortex and the implant cause the release of particles that fracture the surface of the dental implant [5,6].…”
Section: Introductionmentioning
confidence: 99%